Pengembangan Pembelajaran Online Melalui Media Berbasis Google Classroom dalam Meningkatkan Kontinuitas Belajar Siswa di SMA Negeri 3 Kota Jambi - Pratiwi Indah Sari; Kasiono Kasiono (Universitas Batanghari Jambi, 2022)
The link between student learning success with health factors and their physical strength in carrying out activities is none other than due to the existence of activity restriction procedures by the government since the onset of the Covid-19 virus. These activity restrictions do not only affect the economic and political sectors, but also the education sector. Where, the impact and consequences felt by educators, students and parents are quite significant and ultimately lead to various kinds of pros and cons to the implementation of education itself. However, the continuity of learning cannot be fully controlled by the school through the subject matter teachers themselves, but there is cooperation from parents and guardians of students in supervising so that continuity and children's learning activities at home can be maintained in the long term. This is because, when a child studies at home, there are many factors that can encourage their enthusiasm for learning to decrease, so that in the end teaching and learning activities are sufficient and only take place at that time and there is no continuous learning continuity. Thus, as has been known together and in general, that the use of learning media and educational media can overcome the problems that occur, both to increase creativity and skills, as well as the competence of teachers in the field of study, of course, to be able to attract students' interest and attention to the learning materials that are taught. be delivered. In addition, during the ongoing pandemic and the existence of policies through health protocols for the common good, online learning and using media based on Google Classroom can improve the continuity of student learning on an ongoing basis.